PENGARUH MOTIVASI, DISIPLIN KERJA DAN KOMPETENSI TERHADAP KINERJA PEGAWAI BAGIAN UMUM SEKRETARIAT DAERAH KABUPATEN ACEH SELATAN - Sumarni, Dina (AKSIOMA : Jurnal Manajemen, 2022)
In organization, employee performance is an activity that needs to be considered an organizational effectiveness. The purpose of the study to understands the effect of motivation, Disiplin and Competence on employee performance in the General Section of regional secretariat of South Aceh Regency. This method is carried out using quantitative methods by means of systematic data measurement to determine the relationship of the variables to be tested. The data collection method used is a questionnaire in the form of a likert scale, the questionnaire will be given to 32 respondents who have become the research sample, while those that will be tested are validity, reliability and hypotheses. Form the results of multiple linear research concluded that there is a positive influence on employee performance. The result of the t test shows that motivation has no effect on employee performance, While work Discipline and Competence have a positive effect on employee performance. The result of the F test analysis shows that Motivation, Discipline and Competence together a affect employee performance. The results of the test show the correlation coefficient value of 0,667 or 66,7% and the coefficient of determination of 0,445%, then employee performance is influenced by Discipline and Competence.